DEVELOPMENT OF DIGITAL-BASED LKPD ON THE MATERIAL OF ENVIRONMENTAL CONSERVATION EFFORTS TO IMPROVE LEARNING OUTCOMES OF GRADE V STUDENTS - Alfisah, Indra (Edelweiss : Journal Of Innovation In Educational Research, 2025)
The purpose of the research is to develop digital LKPD based on environmental conservation material. This research is a research and development. This research uses the 4-D development model which consists of four stages, namely: define, design, development, and dissemination. The research was conducted at MIS Panca Dharma. The subjects in the study were MIS Panca Dharma fifth grade students in the 2022/2023 school year which totaled 17 students consisting of 12 female students and 5 male students. The object of research is digital-based LKPD. Techniques in research are observation, interviews, questionnaires and documentation. Based on the results of media expert validation with a percentage of 86.37% categorized as valid, the results of language expert validation with a percentage of 96.43% categorized as valid, and the results of material expert validation with a percentage of 90.9% categorized as valid. Based on the results of the pretest trial, it is known that 50% consists of 15 low students and 2 students who have very high scores. Meanwhile, the results of the posttest trial showed that 86% consisted of 16 students who had very high scores and 1 student who had low scores. Student response to digital-based LKPD is 90.9% categorized as very interesting. Based on these results, it can be concluded that digital-based LKPD on the material of environmental conservation efforts to improve the learning outcomes of fifth grade students of MIs Panca Dharma.